Lipase-catalyzed ethanolysis for biodiesel production of untreated palm oil mill effluent. Issue 3 (13th January 2020) - Rachmadona, Nova; Amoah, Jerome; Quayson, Emmanuel; Hama, Shinji; Yoshida, Ayumi; Kondo, Akihiko; Ogino, Chiaki
Abstract : Scheme of palm oil mill effluent (POME) as a feedstock for biodiesel production. Abstract : Palm oil mill effluent (POME), a liquid waste from the palm oil industry, presents an alternative source for biodiesel production without interfering with food supply. This study attempted to produce biodiesel from untreated POME with aqueous ethanol using Thermomyces lanuginosus lipase as a biocatalyst. The effects of enzyme concentration, alcohol to oil ratio, and ethanol concentration were considered in the transesterification reaction. The optimum conditions were 2100 U lipase loading, 4 : 1 ethanol to oil molar ratio, and 45% (v/v) ethanol concentration at 40 °C reaction, and under 24 hours. The maximum fatty acid ethyl ester (FAEE) yield reached 97.43% (w/w) under these conditions. Integration of dilute ethanol for the conversion of POME to biodiesel could be promising as both feedstocks could be obtained from the same location, and thus reduce the logistical burden on biodiesel production.